Esquema de Metadatos para Contenidos Educativos de VoD: Un Enfoque Basado en Competencias Educativas - Guzmán-Delgado, David Mauricio; Chinchajoa-Taimal, Johnny Andres; Duran-Dorado, Diego Fabián; Chanchí-Golondrino, Gabriel Elías; Arciniegas-Herrera, Jose Luis (Revista Científica, 2017)
This paper describes the metadata schema CVoDM, which is a TV-Anytime application profile. CVoDM provides a guidance for the description of Video on Demand (VoD) contents with a special focus on their properties associated to educational competencies. In addition, a tool based on the CVoDM scheme that facilitates VoD contents description is presented, which is useful for generating educational contents repositories. The results of an evaluation support the validity of CVoDM scheme for describing competencies and its accuracy on contents retrieval tasks.